The Influence of Topography on East African October to December Climate: Sensitivity Experiments with RegCM4 - Ogwang, Bob Alex; Chen, Haishan; Li, Xing; Gao, Chujie (Advances in Meteorology, 2014)
The influence of topography on east African climate is investigated using the International Centre for Theoretical Physics Regional Climate Model, with focus on October to December season. Results show that the mean rainfall (temperature) significantly reduces (increases) over the region when topography elevation is reduced. Based on the model, when topography over the selected region (KTU) is reduced to 25%, the mean rainfall (temperature) over east Africa is reduced (increased) by about 19% (1.4°C). The maximum rainfall (temperature) reduction (increase) is however observed around the region over which topography is reduced. The reduction in topography elevation resulted in an anomalous moisture divergence at low level and descending motion over the region. KTU topography enhances the surface heat flux over KTU region and tends to enhance convection over both KTU and the east African region. The topography also helps in the generation of the high frequency mesoscale and subsynoptic disturbances over the region. These disturbances produce precipitation over the region and may also enhance precipitation systems over remote areas due to propagation of the disturbances. The magnitude of the zonal wind speed at 850 hpa increases with the decrease in topography elevation.